2021
DOI: 10.1093/icesjms/fsab007
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Arctic suitable habitat model for Greenland halibut

Abstract: Deep-sea marine fishes support important fisheries but estimates of their distributions are often incomplete as the data behind them may reflect fishing practices, access rights, or political boundaries, rather than actual geographic distributions. We use a simple suitable habitat model based on bottom depth, temperature, and salinity to estimate the potential distribution of Greenland halibut (Reinhardtius hippoglossoides). A large presence-only dataset is examined using multivariate kernel densities to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
13
0
1
Order By: Relevance
“…Greenland Halibut, Reinhardtius hippoglossoides (Walbaum, 1792), is a highly-migratory (Vihtakari et al, 2022), cold-water, long-lived, slow-growing, and economically valuable groundfish (DFO, 2021) with a circumpolar distribution throughout the Northern Hemisphere (Vihtakari et al, 2021). It supports several commercial fisheries throughout the Arctic and the North Atlantic oceans as well as in the Estuary and Gulf of Saint Lawrence (EGSL), Canada (Bowering and Brodie, 1995;Bowering and Nedreaas, 2000;Treble et al, 2008;Delaney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Greenland Halibut, Reinhardtius hippoglossoides (Walbaum, 1792), is a highly-migratory (Vihtakari et al, 2022), cold-water, long-lived, slow-growing, and economically valuable groundfish (DFO, 2021) with a circumpolar distribution throughout the Northern Hemisphere (Vihtakari et al, 2021). It supports several commercial fisheries throughout the Arctic and the North Atlantic oceans as well as in the Estuary and Gulf of Saint Lawrence (EGSL), Canada (Bowering and Brodie, 1995;Bowering and Nedreaas, 2000;Treble et al, 2008;Delaney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Greenland halibut ( Reinhardtius hippoglossoides , Walhaum, 1792; also known as Greenland turbot or black halibut) is a large flatfish distributed primarily in arcto‐boreal cold and deep waters, with continuous populations along continental slopes of the North Pacific, Atlantic, and Arctic Oceans (Hedges et al, 2017; Vihtakari et al, 2021). The species exhibits strong sexual dimorphism with females growing larger (~120 cm vs. 70 cm), older (>30 years vs. >20 years; Treble et al, 2008), and maturing later (L/A50 61 cm/15 years vs. 44 cm/8 years; Morgan et al, 2003; Yan et al, 2022) than males (estimates from the Institute of Marine Research (IMR) database).…”
Section: Introductionmentioning
confidence: 99%
“…Mark–recapture studies have shown that Greenland halibut can be a highly migratory species (Albert & Vollen, 2015; Boje, 2002; Vihtakari et al, 2022). The species inhabit depths of 50–2000 m and temperatures between −2 and 8°C (Bowering & Nedreaas, 2000; Vihtakari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations